A review study on the effect of printing parameters of fused deposition modelling (fdm) metal polymer composite parts on mechanical properties and surface roughness - Sukindar, Nor Aiman; Md Azhar, Muhammad Afif; Syed Shaharuddin, Sharifah Imihezri; Kamaruddin, Shafie; Ahmad Azhar, Ahmad Zahirani; Yang, Chuan Choong; Triblas Adesta, Erry Yulian (Universiti Putra Malaysia, 2022)
Fused deposition modelling (FDM) is a three-dimensional (3D) printing method under the additive manufacturing process. The process of FDM runs by depositing a melted filament which is a built material, layer by layer on a printing bed. This paper intends to sum up the latest research findings in recent years on the effects of printing parameters on the mechanical properties and surface roughness of 3D-printed metal polymer parts via FDM based on reported literature. Recently, various types of materials have been made and used as build materials that have their functions and properties. Metal polymer composite is considered as a new type of material for FDM which offers a wide range of applications in the manufacturing industry. The use of metal composite in FDM has been challenging due to several shortcomings in terms of mechanical properties and surface roughness of the printed part. Due to the anisotropic feature of an FDM printed part, the mechanical properties of the specimen are affected such as tensile strength and flexural while different types of materials are used to give different surface finishes on the printed part. Additionally, the mechanical properties and the surface roughness are also influenced by the printing parameters where the manipulation or adjustment on these parameters will give different results on these two properties. The layer thickness, infill density, raster angle, and printing temperature are among the printing parameters that can be altered. The use of optimal printing parameters for the metal composite can produce high-quality products and be able to contribute to developments in the manufacturing industry in the future. Therefore, a review study on the effect of printing parameters of FDM metal polymer composite parts on the mechanical properties and surface roughness was carried out.